2012
DOI: 10.1007/s12010-012-0021-1
|View full text |Cite
|
Sign up to set email alerts
|

Short Hairpin RNA-Induced Myostatin Gene Silencing in Caprine Myoblast Cells In Vitro

Abstract: Myostatin (MSTN) belongs to the transforming growth factor (TGF)-β superfamily and is a potent negative regulator of skeletal muscle development and growth. Dysfunction of MSTN gene either by natural mutation or induced through genetic manipulation (knockout or knockdown) has been reported to increase the remarkable muscle mass in mammalian species. RNA interference (RNAi) is the most promising method for inhibition of gene expression that can be utilized for MSTN gene knockdown by developing short hairpin RNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…According to McGivney et al (2012) and Tripathi et al (2013), the muscle growth process unites hyperplasia and hypertrophy, and is regulated by myogenic factors. Myostatin is a member of the genes of the transforming growth factor beta (TGF-β).…”
Section: Discussionmentioning
confidence: 99%
“…According to McGivney et al (2012) and Tripathi et al (2013), the muscle growth process unites hyperplasia and hypertrophy, and is regulated by myogenic factors. Myostatin is a member of the genes of the transforming growth factor beta (TGF-β).…”
Section: Discussionmentioning
confidence: 99%
“…Our observations indicated that the four MEF2 genes in the ricefield eel at earlier development (sizes: 5–45 g) were all upregulated; these perhaps implied that they had cooperative action, which is according to that reported by Potthoff and Olson (). This could indicate that myoblast proliferation and differentiation during the initial growth phases could be inferred by the high expression levels of the MEF2 gene family (Hu et al ; Tripathi et al ). Thus, the data obtained further our understanding of molecular processes between muscle cell differentiation and growth and MEF2 gene family regulation function in fish, at least in the ricefield eel.…”
Section: Discussionmentioning
confidence: 99%
“…The transgenic goat having myostatin knocked down offers the potential to enhance the meat production. To achieve this objective, earlier, we and other group reported successful knockdown of MSTN in in vitro culture system using shRNA against MSTN gene through transient transfection assay . The current study aimed to examine whether a plasmid vector, expressing myostatin‐targeting shRNA, could be able to continuously suppress endogenous MSTN expression after integrating into the genome of GFF cells.…”
Section: Introductionmentioning
confidence: 99%